Enhancing Cyber-attacks Awareness Via Mobile Gamification Techniques - Sakinah Ali Pitchay; Farida Hazwani Mohd Ridzuan; Azni Hazlizan Ab Halim; Anis Syahira Suhaimi; Najwa Hayaati Mohd Alwi (Asian Scholars Network, 2024)
Volume: 4 No: 2 (page: 69-84)